TALENT IDENTIFICATION, COMPLEX PERFORMANCE DIAGNOSTIC PROTOCOL IN BASKETBALL - Balogh, László; Rátgéber, László; Nagy, Dóra (Stadium - Hungarian Journal of Sport Sciences, 2025)
If we want to gain a competitive advantage over our domestic and international competitors in continuous competition, the first task is to filter and select the sport or the given sport correctly. Later based on the current results of sports science, it is necessary to consistently, consciously, complete the complex, time-consuming process of talent management. Selection process requires a lot of patience and perseverance. The aim of talent identification is to select children in sports with specific skills that can be systematically transformed into practice.. It is necessary to measure complex, sport-specific components of performance. Researchers in a meta-analysis of talent identification protocols in team sports found that physical parameters such as height, body weight, body composition, and physiological capacities such as aerobic capacity, anaerobic strength, strength, coordination, and agility play a role. On the other hand, the quality of specific psychological-mental skills is also critical in identifying talents.